Endoscopic ultrasound and paracentesis in the evaluation of small volume ascites in patients with intra-abdominal malignancies - Montgomery, Marissa M (Baishideng Publishing Group Inc, 2014)
The evaluation of ascites in patients with known or suspected malignancy is a critical aspect of preoperative staging. Endoscopic evaluation by ultrasound of low volume ascites and sampling of the ascitic fluid by endoscopic ultrasound guided paracentesis (EUS-P) is both a sensitive and specific modality for the determination of peritoneal implants, which is not only an important prognostic indicator but a crucial factor in determining treatment strategy. It is common practice to utilize EUS for gastrointestinal malignancies such as pancreatic or gastric masses, with the performance of paracentesis during the same procedure for the purpose of imaging the abnormality and possibly performing fine needle aspiration for biopsy of the neoplasm itself. However, given the ability of EUS-P to adequately sample even minimal ascites, detecting much smaller volumes than traditional computed tomography or magnetic resonance imaging, EUS-P may be a useful modality for the standard metastatic workup of any newly diagnosed or suspected malignancy. In this “Field of Vision” commentary, we discuss the role of EUS-P, including the article by Suzuki et al reporting their experience with EUS-P using an automated spring-loaded needle device. We also review the utility of EUS-P for non-gastrointestinal malignancies, such as ovarian cancer, which has a high incidence of malignant ascites.